2001
DOI: 10.1007/s11882-001-0021-7
|View full text |Cite
|
Sign up to set email alerts
|

Surgical intervention for sinusitis in children

Abstract: Pediatric rhinosinusitis represents a common endpoint of many potential etiologic factors, but fixed anatomic obstruction of sinus outflow is relatively unusual in pediatric patients. Surgical therapy is considered when medical therapy for underlying mucosal inflammation fails. Adenoidectomy is usually the first surgical intervention to be considered for young children, with the goal of improving sinus drainage and eliminating a potential source of bacteria. Endoscopic sinus surgery is considered for the small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…There seems to be a consensus favoring surgical intervention in children with refractory CRS who fail medical management. However, there is still disagreement about which type of surgical intervention is appropriate 2,4–11 . Adenoidectomy 4–6 and ESS 7,8,11 have both been recommended as surgical options 4–6 .…”
Section: Discussionmentioning
confidence: 99%
“…There seems to be a consensus favoring surgical intervention in children with refractory CRS who fail medical management. However, there is still disagreement about which type of surgical intervention is appropriate 2,4–11 . Adenoidectomy 4–6 and ESS 7,8,11 have both been recommended as surgical options 4–6 .…”
Section: Discussionmentioning
confidence: 99%
“…Lusk and Muntz 41 and Gross et al 79 reported favorable results in endoscopic sinus procedures in children. Others confirmed these results 31,37,39,40,46,80–91 …”
Section: Discussionmentioning
confidence: 72%
“…Core cultures of adenoid tissue show pathogens similar to rhinosinusitis and are independent of the size of the adenoid pad 59 . Adenoidectomy is now considered an appropriate first step when medical management fails 31 . In general, the efficacy of adenoidectomy in treating chronic pediatric rhinosinusitis is approximately 48% to 75% 37–39,60 .…”
Section: Discussionmentioning
confidence: 99%
“…It removes the obstruction as well nidus of infection [118–121]. A risk-benefit analysis should be carried out before considering other surgical approaches in children.…”
Section: Managementmentioning
confidence: 99%